2018
DOI: 10.1002/admt.201800205
|View full text |Cite
|
Sign up to set email alerts
|

A Fluorescence Intensity Ratiometric Fiber Optics–Based Chemical Sensor for Monitoring pH

Abstract: Accurate determination of pH is essential, yet a single technology is relied upon for almost all pH measurements. Here, a new optical pH sensor is described. Two highly photostable fluorescent dyes with a polymerizable side chain are incorporated into a composite polymer that allows for fast transport of protons. A pH‐responsive dye and a reference dye with limited response to pH are used, thus allowing for determining pH using a ratiometric fluorescence intensity response. The sensor material—dyes covalently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 54 publications
0
28
0
Order By: Relevance
“…In summary, we have shown that triangulenium-based dyes can be converted to redox probes by linking them to a redox sensitive motif. High photostability, long decay times and high yield synthesis are some of the arguments to further investigate triangulenium based indicators for sensor development [41,[50][51][52] as well as imaging purposes.…”
Section: Resultsmentioning
confidence: 99%
“…In summary, we have shown that triangulenium-based dyes can be converted to redox probes by linking them to a redox sensitive motif. High photostability, long decay times and high yield synthesis are some of the arguments to further investigate triangulenium based indicators for sensor development [41,[50][51][52] as well as imaging purposes.…”
Section: Resultsmentioning
confidence: 99%
“…While only a few research studies have examined DCS [119,[121][122][123], chemical sensing materials are being studied for a wider variety of optical fiber applications, which could theoretically be used for the production of DCS to track corrosive external factors. For compatibility with OFS, there are a number of pH-sensing materials, including localized surface plasmon resonance (LSPR) Au or Ag nanoparticles (NP) integrated composites (Figure 13a) [124][125][126], organic dyes [127][128][129][130][131][132], fluorescent molecules [133][134][135][136][137], polymers [138][139][140][141], pH-sensitive hydrogel [142][143][144][145], etc. The pH value of the solution independent of the material embedded in the matrix is observed to be more integrated with the silica matrix coating [124,146].…”
Section: Distributed Ofs For Chemical Sensingmentioning
confidence: 99%
“…However, the decrease of the band at 660 nm is due to the overlap with the peak 595nm, as it has been confirmed DMQA has no fluorescence response to pH when it is in the gel phase. 41 The normalized and smoothed fluorescence spectra were shown in Figure S5, and the pH is evaluated by the ratiometric signal of the integrated peak areas (DAOTA/DMQA). By monitoring the sensors response to pH, we could see the responses are reversible and repeatable (Figure S6).…”
Section: Sensor Materials Synthesismentioning
confidence: 99%
“…21,40 We have described an organically modified silicon sol-gel that solves many of these issues, when it comes to creating a competitive optical pH sensor. 3,18,[41][42][43] The resulting sensor material has good chemical, photochemical and thermal stability as well as fast diffusion of H + , while excluding all other ions. The sensor material has the capacity to fully encapsulate the pH responsive dye, the ability to firmly stick to polymer and glass substrate, a long shelf-life and is fully biocompatible.…”
Section: Introductionmentioning
confidence: 99%